"تفضیلات الشيخ سيد أمير علي ملیح آبادی فی تفسیر القرآن: دراسۃ"مواھب الرحمن: Preferences of Syed Amīr ʻAlī Malīḥabādī in Qur’ānic Exegesis: A Study of “Mawāhib al-Raḥmān” (Al-Qamar, 2018)
This paper explores the preferences adopted by Syed Amīr ʻAlī Malīḥabādī in his exegesis of the Quran named “Mawāhib al-Raḥmān.” Giving a biographical sketch of the author, this research investigates his exegetical methodology. It finds that while interpreting the Qur’ānic verses the commentator provides arguments from Quran, Ḥadīth, sayings of companions and their disciples and successors. An important feature of his commentary is that he, after quoting the opinions of other prominent scholars, gives his preference about the most accurate opinion. This kind of exegesis has been made in all issues like issues related to creeds, jurisprudence etc.
Keywords: Exegesis; Amīr ʻAlī; Mawāhib al-Raḥmān; preferences